Bene?t sharing mechanisms. Agreements for watershed wellbeing - Consorcio para el Desarrollo Sostenible de la Ecorregion Andina (CONDESAN, 2011)
The instruments that we propose for the equitable distribution of environmental benefits in the Andean basins are based on dialogue and social consensus mechanisms and not only in the payment for environmental services. As a starting point for discussion and consensus is essential investment in scientific research and monitoring, to enable diagnoses have clear intervention areas and proposals that generate tangible benefits for the actors of the basins.